2017
DOI: 10.1002/qua.25449
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the stability and properties of magic numbers (m = 5, n = 2) and (m = 6, n = 3) of bimetallic bismuth‐copper nanoclusters; Bim Cun

Abstract: Inspired by the experimental discovery of magic numbers we present a first study using density functional theory for the structure and properties of neutral and cationic Bi6Cu3 and Bi5Cu2 clusters. Our results confirm predictions based on Wade's rules. The closed electron shells, characteristic of cationic clusters help impose enhanced stability, while also complying with Wade's rules. Charge distribution analysis, as well as electrostatic potential maps show that in almost all cases, Bi atoms donate charges t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…They also complement the allotropes of a particular element, such as chains, rings, sheets, and bulk networks, just to mention some possibilities . The study of transition metal clusters (TMCs) has been relevant for both experimental and theoretical approaches because of their unusual structural, magnetic, electronic, and catalytic properties in comparison to their macroscopic analogs or individual atoms. Experimental advances on the synthesis and characterization of TMCs through molecular beams in the gas phase have made possible a more complete study of these nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…They also complement the allotropes of a particular element, such as chains, rings, sheets, and bulk networks, just to mention some possibilities . The study of transition metal clusters (TMCs) has been relevant for both experimental and theoretical approaches because of their unusual structural, magnetic, electronic, and catalytic properties in comparison to their macroscopic analogs or individual atoms. Experimental advances on the synthesis and characterization of TMCs through molecular beams in the gas phase have made possible a more complete study of these nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, transition bimetallic clusters have received increasing attention owing to their different physical and chemical properties compared to their pure counterparts. [1][2][3][4][5][6][7] Because of their unique properties, these bimetallic clusters can be utilized in various technological applications such as catalysis, electronics, and medicine, among others. [8][9][10] Specifically, in the field of catalysis, interest in NiCu bimetallic nanoparticles has steadily grown, largely due to their promising catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…33−36 Specifically, recent articles of copper−bismuth binary systems provide an insight into the intermetallic dynamics. 37,38 Also, the combined experimental and theoretical study for tin−bismuth clusters was reported by Heiles et al 39,40 Bimetallic cluster with gold 41−45 has attracted more attention as small gold clusters are known to possess unique catalytic properties. 46 We are aware of only two theoretical studies on neutral gold−bismuth clusters.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous investigations on bismuth clusters doped with main group elements, , and a few theoretical studies of bimetallic clusters of bismuth with transition metals have been reported. Specifically, recent articles of copper–bismuth binary systems provide an insight into the intermetallic dynamics. , Also, the combined experimental and theoretical study for tin–bismuth clusters was reported by Heiles et al , Bimetallic cluster with gold has attracted more attention as small gold clusters are known to possess unique catalytic properties . We are aware of only two theoretical studies on neutral gold–bismuth clusters. , Our previous PES study of AuBi – and BiBO – revealed similarity in the electronic structure and bonding of gold and boronyl to bismuth …”
Section: Introductionmentioning
confidence: 99%